MAGT1 is required for HeLa cell proliferation through regulating p21 expression, S-phase progress, and ERK/p38 MAPK MYC axis. Issue 21 (2nd November 2021) - Bi, Caili; Zhang, Xue; Chen, Yueyue; Dong, Yushuo; Shi, Yixin; Lei, Yunshen; Lv, Dan; Cao, Xiaowei; Li, Wei; Shi, Hongcan
ABSTRACT: Magnesium transporter subtype 1 (MAGT1) is known to participate in animal development and cell differentiation. Thus far, MAGT1 studies have mainly focused on its role in cardiomyocyte regulation and differentiation; only a few studies have demonstrated its role in cell proliferation. To investigate the underlying mechanism of MAGT1 in cell proliferation, HeLa and SiHa cells were transiently knocked down with different siRNAs. We showed that cell proliferation was substantially restricted by S-phase arrest and apoptosis in the MAGT1-knocked down cells, which was further confirmed by the increased expression of p21, cyclin-A1, and cyclin-B1, as well as the decreased expression of MYC, cyclin-D1, cyclin-E1, and CDK2. MAGT1 knockdown also resulted in significant changes in the transcriptional expression of 1, 598 genes that were analyzed by RNA sequencing. Bioinformatics analysis showed that MAGT1 was related to the MAPK signaling pathway. Western blot analysis confirmed that the phosphorylation of extracellular signal-related protein kinase 1/2 (ERK1/2) and p38 was remarkably reduced in MAGT1 down-regulated groups. Additionally, MAGT1 was required for the function of viral proteins E6/E7 during cell proliferation and G1/S cell-cycle progression. Therefore, MAGT1 plays a crucial role in the proliferation of HPV-positive cervical cancer cells, S-phase progression, and the ERK/p38 MAPK signaling pathway. These results indicate the potential of MAGT1 as a novel target for anticancer research. Abbreviations : MAGT1: Magnesium transporter subtype 1; MAPK: Mitogen-activated protein kinase; XMEN: X-linked immunodeficiency with Magnesium defect, Epstein-Barr virus infection and Neoplasia; BMMSCs: Bone Marrow Mesenchymal Stem Cells; Dpp: Decapentaplegic; CDKIs: CDK inhibitors; GPCR: G-protein coupled receptor; GO: Gene Ontology; KEGG: Kyoto Encyclopedia of Genes and Genomes; RTK: Receptor Tyrosine Kinase; PTK: Protein Tyrosine Kinase; FGFR: Fibroblast Growth Factor Receptor; BMP: Bone Morphogenetic Protein; HPV18 E6/E7: Human Papillomavirus 18 Early protein 6/ early protein 7; FACS: Fluorescence Activated Cell Sorting; PI: Propidium Iodide